The Role of National Councils on Older Adults in Rethinking the Public Institutionality Framework for Human Aging in Latin America - Gutiérrez Murillo, Roberth Steven (2025)
The study presents a theoretical and conceptual review of the regional framework on population aging in Latin America, emphasizing the role of National Councils on Older Adults as governing bodies in this field. It examines their current strengths and challenges, highlighting their importance as key public institutions in the design and implementation of policies related to aging and older adults. Using case studies from Argentina, Brazil, Chile, Costa Rica, and Uruguay, the analysis explores practical experiences that offer valuable lessons for strengthening these entities. This review contributes to updating knowledge about public institutions focused on the stewardship of population aging in the region.